Zoledronic acid and alendronate sodium and the implications in orthodontic movement - Franzoni, J. S.; Soares, F. M. P.; Zaniboni, E.; Vedovello Filho, M.; Santamaria, M. P. [UNESP]; Santos, G. M. T. dos; Esquisatto, M. A. M.; Felonato, M.; Mendonca, F. A. S.; Franzini, C. M.; Santamaria, M. (Wiley-Blackwell, 2017)
Structured Abstract ObjectiveTo evaluate orthodontic tooth movement (OTM) in rats treated with two types of bisphosphonates (BPs), alendronate sodium (A) and zoledronic acid (Z). DesignIn all, 15 male Wistar rats were randomly divided into three groups. Group OTM+A: orthodontic tooth movement and subcutaneous administration of alendronate sodium (2.5mg/kg); Group OTM+Z: orthodontic tooth movement and subcutaneous administration of zoledronic acid (0.02mg/kg), and Group OTM: orthodontic tooth movement and subcutaneous injection of saline. The BPs were administered once a day during 25days before OTM started and during 10days of OTM. The left upper first molar was moved with a stainless-steel closed coil spring which delivered an initial force of 0.4N. OTM was measured with a digital caliper comparing the moved and the contralateral side. The histomorphometric analysis counted the number of osteoclasts, inflammatory cells, blood vessels and fibroblasts (n/10(4)m(2)) in periodontal ligament (PDL) of the distobuccal root. ResultsA reduction of 58.3% of OTM was found in Group OTM+A and 99.6% in Group OTM+Z, when compared with Group OTM. There was a significant decrease of osteoclasts and inflammatory cells in BP-treated groups. Blood vessels and fibroblastic cells decreased mainly in Group OTM+Z. ConclusionAlendronate sodium and zoledronic acid have similar effects on the periodontal tissue during orthodontic treatment in rats. Especially, zoledronic acid can affect orthodontic tooth movement.
Keywords: adverse effects; alendronate sodium; bisphosphonates; orthodontic tooth movement; zoledronic acid